Democratization of managing education in the context of modern trends in higher education development - Kharkivska, A. A. (Problems of Engineer-Pedagogical Education, 2018)
In the article, the author analyzes normative-legal documents (law, strategy, orders, etc.), scientific-pedagogical and special literature and on their basis the processes of democratization of managing education are considered. The focus is on the basis of pedagogical education such as: humanism, fullness, quantitative and qualitative sufficiency, immanence of development, sciencecorrespondence′, continuity, precedence, and democracy. By summarizing the opinions of Ukrainian and foreign scientists and taking into account experience and previous research, the author identified trends in higher education. The researcher comes to the conclusion that the process of democratisation in education should be considered from different angles: firstly, as democratization of management of educational process: the process of training and education, and secondly, as democratization of managing education in general as well as democratization of management of private educational establishments.